Evaluating Functional Performance Tests in those with Non-arthritic Intra-articular Hip Pain: An International Consensus Statement - RobRoy L Martin; Amir Takla; Ashley Disantis; David Kohlrieser; Keelan Enseki; Liran Lifshitz; Louise Grant; Mario Bizzini; Mike Voight; Mark Ryan; Ryan McGovern; Timothy Tyler; et al. (International Journal of Sports Physical Therapy)
# Background